2018
DOI: 10.1016/j.bioactmat.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of a novel SnO2-doped dicalcium phosphate coating on AZ31 magnesium alloy

Abstract: A SnO2-doped dicalcium phosphate coating was prepared on AZ31 alloy by means of hydrothermal deposition. The results showed that the coating possessed a globular morphology with a long lamellar crystalline structure and a thickness of approximately 40 μm. The surface of the coating became smooth with an increase additive amount of the SnO2 nanoparticles. The corrosion current density and hydrogen evolution rate of the coating prepared in presence of SnO2 were reduced compared to the coating without SnO2 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It was observed that the corrosion products consisted of Mg(OH) 2 , SnO 2 and compounds containing Ca/P according to the XRD(Figure S3 (in the Supplementary Materials)) and EDS. SnO 2 will enhance the compactability of corrosion products [40].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the corrosion products consisted of Mg(OH) 2 , SnO 2 and compounds containing Ca/P according to the XRD(Figure S3 (in the Supplementary Materials)) and EDS. SnO 2 will enhance the compactability of corrosion products [40].…”
Section: Resultsmentioning
confidence: 99%
“…However, poor corrosion resistance is one of their fatal disadvantages to hinder their further engineering applications [1][2][3][4][5][6][7]. Usually, coating is an effective means to improve the corrosion resistance of Mg alloys in aqueous solutions and many kinds of techniques have ever been attempted [8][9][10][11]. Compared to chemical methods, most physical methods such as physical vapor deposition and ion implantation are innocuous to environment [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid and uncontrollable corrosion process leads to a significant decrease in mechanical strength of the orthopedic appliance, and finally results in the premature failure of the implants. Many efforts have been taken to enhance the corrosion resistance of magnesium [7][8][9][10][11]. However, it must be taken into account that improving the corrosion resistance of magnesium will lead to the compromise of its antibacterial abilities, which are attribute and proportional to the alkaline pH during its degradation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%